Saving oil in a hurry (OECD/IEA, 2005)
"During 2004, oil prices reached levels unprecedented in recent years. Though world oil markets remain adequately supplied, high oil prices do reflect increasingly uncertain conditions. Many IEA member countries and non-member countries alike are looking for ways to improve their capability to handle market volatility and possible supply disruptions in the future. This book aims to provide assistance. It provides a new, quantitative assessment of the potential oil savings and costs of rapid oil demand restraint measures for transport. Some measures may make sense under any circumstances; others are primarily useful in emergency situations. All can be implemented on short notice if governments are prepared. The book examines potential approaches for rapid uptake of telecommuting, ecodriving, and car-pooling, among other measures . It also provides methodologies and data that policymakers can use to decide which measures would be best adapted to their national circumstances. This tool box may help countries to complement other measures for coping with supply disruptions, such as use of strategic oil stocks."--publisher summary.